Enhancing Student Learning Outcomes through the Card Group Learning Model: An Action Research in Islamic Religious Education - Yuliasmi (Yayasan Darussalam Bengkulu, 2023)
This study investigates the effectiveness of the Card Group learning model in improving student learning outcomes in Islamic Religious Education, specifically in the topic of “Glorifying Allah SWT by Submitting to His Commands.” Conducted with 26 seventh-grade students at SMPN 20 Bengkulu, the research employed classroom action research (CAR) across two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected using tests, observation, documentation, and interviews, and analyzed through descriptive statistics and percentage of mastery learning. Findings revealed a significant improvement in student outcomes: the average score increased from 54.23 (pre-cycle) to 76.08 (cycle I) and 80.81 (cycle II). Mastery learning rose from 15.38% (pre-cycle) to 80.78% (cycle I) and reached 100% in cycle II. The results confirm that the Card Group model enhances student engagement, promotes collaborative learning, and fosters deeper understanding of Islamic values. This research contributes to the growing body of literature on active learning strategies in religious education and provides practical implications for teachers seeking innovative methods to improve student achievement.